A80G polymorphism of reduced folate carrier 1 (RFC1) and C776G polymorphism of transcobalamin 2 (TC2) genes in Down’s syndrome etiology - Biselli, Joice Matos (2008)
CONTEXT AND OBJECTIVE: There is evidence that polymorphisms of genes involved in folate metabolism may be associated with higher risk that mothers may bear a Down’s syndrome (DS) child. This study therefore had the objective of investigating the A80G polymorphism of the reduced folate carrier 1 (RFC1) gene and the C776G polymorphism of the transcobalamin 2 (TC2) gene as maternal risk factors for DS among Brazilian women. DESIGN AND SETTING: Analytical cross-sectional study with control group, at Faculdade de Medicina de São José do Rio Preto (Famerp). METHODS: Sixty-seven mothers of DS individuals with free trisomy 21, and 113 control mothers, were studied. Molecular analysis of the polymorphisms was performed by means of the polymerase chain reaction with restriction fragment length polymorphism (PCR-RFLP), followed by electrophoresis on 2% agarose gel. RESULTS: The frequencies of the polymorphic alleles were 0.51 and 0.52 for RFC1 80G, and 0.34 and 0.34 for TC2 776G, in the case and control groups, respectively. Thus, there were no differences between the groups in relation to either the allele or the genotype frequency, for both polymorphisms (P = 0.696 for RFC1 A80G; P = 0.166 for TC2 C776G; P = 0.268 for combined genotypes). CONCLUSION: There was no evidence of any association between the RFC1 A80G and TC2 C776G polymorphisms and the maternal risk of DS in the sample evaluated.